Eloquence embodied nonverbal communication among French & indigenous peoples in the Americas - Carayon, Céline (Omohundro Institute of Early American History and Culture, 2019)
"Taking a fresh look at the first two centuries of French colonialism in the Americas, this book answers the long-standing question of how and how well indigenous Americans and the Europeans who arrived on their shores communicated with each other. French explorers and colonists in the sixteenth century noticed that indigenous peoples from Brazil to Canada used signs to communicate. The French, in response, quickly embraced the nonverbal as a means to overcome cultural and language barriers. Céline Carayon's close examination of their accounts enables her to recover these sophisticated native practices of embodied expressions"--Provided by publishe